Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1007/bf01617806
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative oxidation of nutrients in growing calves

Abstract: The present paper deals with the possibility of using measurements of CH4 production in growing calves to estimate the amount of CO2 produced by fermentative processes and to calculate the oxidation of nutrients. Twenty bull calves were fed diets with varying proportions of corn grain and forage. The protein and energy metabolism was measured in 118 individual balance trials in the live weight range of 120-350 kg by means of indirect calorimetry and carbon-nitrogen balances. The values of oxidized carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 3 publications
4
20
0
Order By: Relevance
“…Chwalibog et al (1997) reported that RQnpx lower than 1 indicates predominance of OXF vs. OXCHO, and under positive energy balance, part of the OXF should originate from ingested carbohydrate (mainly fibre) and diet fat content.…”
Section: Energy Balance and Oxidation Of Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chwalibog et al (1997) reported that RQnpx lower than 1 indicates predominance of OXF vs. OXCHO, and under positive energy balance, part of the OXF should originate from ingested carbohydrate (mainly fibre) and diet fat content.…”
Section: Energy Balance and Oxidation Of Nutrientsmentioning
confidence: 99%
“…Energy associated with the oxidation of protein (OXP), carbohydrate (OXCHO) and fat (OXF) was calculated by the method of Brouwer (1958) and Chwalibog et al (1997) Then, the HP from oxidation (HPx) was:…”
Section: Calculationsmentioning
confidence: 99%
“…Indirect calorimetry based on measurements of gas exchange has been used successfully during the last century in order to estimate energetic values of feedstuffs and animals' requirement for nutrients and energy. Recently, measurements of gas exchange have been used to calculate nutrient oxidation and lipogenesis in the intact body of man , pigs (CHWALIBOG et al 1992;CHWALIBOG and THORBEK 1995), calves (CHWALIBOG et al 1996;CHWALIBOG et al 1997a), mink (TAUSON et al 1997) and rats (CHWALIBOG et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The energy associated with the oxidation of protein (OXP), carbohydrate (OXCHO) and fat (OXF) was calculated by the method of and Chwalibog et al (1997) for ruminants. The CO 2 production from oxidation (CO 2x ) was calculated as CO 2 -(2  CH 4 ), according to Fahey and Berger (1988).…”
Section: Calculationsmentioning
confidence: 99%
“…The HE was determined from measurements of O 2 consumption, CO 2 and CH 4 production, and urine N (Nur), using the equation [16]: The energy associated with the oxidation of protein (OXP), carbohydrate (OXCHO) and fat (OXF) was cal-culated by the method of [17] and [18] for ruminants. The production of volatile fatty acid from carbohydrate fermentation is followed by CO 2 and CH 4 production.…”
Section: Calculationsmentioning
confidence: 99%